(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
We take Opportunity to present this paper of „Performance curve and Emission Characteristics using alternative fuels Ethanol and Biodiesel in turbocharging Diesel engine’ and put before readers some useful information regarding our project. We have made since attempts and taken every engineer to present this matter in precise and compact form ,the language being as simple as possible. We are sure that the information contained in this volume would certainly prove useful for better insight in the scope and dimension of this project in its true perspective. The task of completion of project through being difficult was made quit simple, interesting and successful. Drawan by a list of priorities like fast decreasing oil resourses.We are going to use alternative fuels Ethanol and Biodiesel in turbocharging Diesel engine It will increase overall system efficiency and save considerable amount of money by decreasing of fuel consumption accordingly.